PERLINDUNGAN HUKUM TERHADAP PENGGUNA VTUBE DI INDONESIA - Ni Komang Sri Jayanti; Eduardus Bayo Sili; I Gusti Agung Wisudawan (Bagian Hukum Bisnis Fakultas Hukum Universitas Mataram, 2021)
This thesis has the purpose to find out how the business investigation regulation for the Future View Tech (VTube) in Indonesia and how the legal responsibility of the Future View Tech (VTube) against VTube application users in Indonesia. The research method in this study uses normative legal research. The purpose and the benefit of this study are that the public can find out the investment business regulations through the Future View Tech (VTube) application and the legal responsibility of the Future View Tech (VTube) against the users of VTube who have already used the application. This could be a reference for the people for the legal protection of users against illegal applications on social media, especially the users of the VTube application. The result of this study showed that the VTube application developed by the PT Future View Tech who work in the advertising business is declared illegal by Investment Readiness Task Force (SWI) The Financial Services Authority (OJK) with SP Number 06/VII/2020 decisions since 03 June 2020, because Vtube is not eligible. The legal responsibility company against Vtube users that they are identity getting protection by Kominfo and the development of VTube have been doing by preventive and repressive legal protections.